Ethical Principles in Public Health Research: Contextual Understanding with Islamic Legal Principles - Faradilla Diwanta; Irwansyah Irwansyah; Faiqah Adnin Purba (LPPM UIKA Bogor, 2024)
This research explores the role and significance of ethical principles in the context of societal research, with particular emphasis on Islamic legal perspectives. Through contextual analysis, this research identifies relevant ethical principles and applies the Islamic legal framework as a moral foundation. The problem was motivated by cases of ethical lapses in health research. Not only does this happen in foreign countries, but in Indonesia, there are also frequent ethical lapses in health research. An important event that opened the eyes of the whole world and embarrassed the scientific community was the Doctor's Trial, which was carried out in the city of Nuremberg, Germany, after the end of World War II. The Doctor's Trial was a series of trials held after World War II to try individual Nazis for war crimes and crimes against humanity. The Doctor's Trial specifically highlights the medical crimes committed by Nazi doctors. Apart from that, there were also irregularities that occurred at Tuskegee, namely that medication was not given to participants after the research was carried out, resulting in seven people dying and 150 people suffering from heart failure. Not only that, the problem of violations of research ethics also occurred in Indonesia, namely research on the drug